2016
DOI: 10.1002/anie.201609080
|View full text |Cite
|
Sign up to set email alerts
|

Engineering the Electrical Conductivity of Lamellar Silver‐Doped Cobalt(II) Selenide Nanobelts for Enhanced Oxygen Evolution

Abstract: Precisely engineering the electrical conductivity represents a promising strategy to design efficient catalysts towards oxygen evolution reaction (OER). Here, we demonstrate a versatile partial cation exchange method to fabricate lamellar Ag-CoSe nanobelts with controllable conductivity. The electrical conductivity of the materials was significantly enhanced by the addition of Ag cations of less than 1.0 %. Moreover, such a trace amount of Ag induced a negligible loss of active sites which was compensated thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
98
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 183 publications
(104 citation statements)
references
References 38 publications
6
98
0
Order By: Relevance
“…[3,4] State-of-the-art OER catalysts are typically precious-metal-based catalysts, such as ruthenium (Ru) and iridium (Ir) oxides, in which the high cost and low abundance features limits the large-scale application. [5] Thus, it is desirable to develop costeffective and earth-abundant materials as OER catalysts for high-efficient performance.Up to now, many types of transition-metal based materials have been explored as OER electrocatalysts, such as sufides, [6,7] selenides, [8,9] (oxy)hydroxides, [10,11] and phosphides. [12,13] Recent studies found that monometallic nitrides, such as Ni 3 N, CoN, Co 4 N are appealing noble-metal-free catalysts for OER, since their approximate zero-valent metallic-like feature, and low cost.…”
mentioning
confidence: 99%
“…[3,4] State-of-the-art OER catalysts are typically precious-metal-based catalysts, such as ruthenium (Ru) and iridium (Ir) oxides, in which the high cost and low abundance features limits the large-scale application. [5] Thus, it is desirable to develop costeffective and earth-abundant materials as OER catalysts for high-efficient performance.Up to now, many types of transition-metal based materials have been explored as OER electrocatalysts, such as sufides, [6,7] selenides, [8,9] (oxy)hydroxides, [10,11] and phosphides. [12,13] Recent studies found that monometallic nitrides, such as Ni 3 N, CoN, Co 4 N are appealing noble-metal-free catalysts for OER, since their approximate zero-valent metallic-like feature, and low cost.…”
mentioning
confidence: 99%
“…For NCF450, a strong peak for hydroxide was observed, which confirmed the growth of CoFe LDH on the Ni/NiO surface . Two main peaks at 781.1 and 797.1 eV were observed in the high‐resolution XPS spectrum of Co 2p, which corresponded to the binding energy of Co 2p 3/2 and Co 2p 1/2 , respectively, and there were two satellite peaks located at 786.3 and 802.6 eV . The difference between Co 2p 3/2 and Co 2p 1/2 represents a spin orbital splitting energy of approximately 16 eV, confirming that the Co element was primarily presented as Co 2+ .…”
Section: Resultsmentioning
confidence: 99%
“…TheX-ray diffraction (XRD) patterns in Figure 1a reveal an obvious transformation of crystalline structure from cubic phase (JCPDS No.0 9-0234) for pristine c- 15] Additionally,t he diffraction intensity becomes much weaker,i ndicating the successful exfoliation. [16] By contrast, in final o-CoSe 2 -O UNs,anew peak at 174 cm À1 ,c haracteristic signature of orthorhombic phase,e merges and the pristine four peaks are appreciably weakened and broadened, rooting from the surface structural disorder and atomic vacancies ( Figure 1b). [16] By contrast, in final o-CoSe 2 -O UNs,anew peak at 174 cm À1 ,c haracteristic signature of orthorhombic phase,e merges and the pristine four peaks are appreciably weakened and broadened, rooting from the surface structural disorder and atomic vacancies ( Figure 1b).…”
Section: Angewandte Chemiementioning
confidence: 98%